Peran Komunikasi Interpersonal Orang Tua Dual Career Marriage di Surabaya dalam Mengawasi Pembelajaran Daring Anak Remaja Awal di Masa Pandemi Covid-19 - Syadza Nadhira Attya P; Saifuddin Zuhri (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Interpersonal communication is one of the communications commonly used to convey persuasive messages and increase intimacy as well as a form of communication that can be a bridge for expressing a thought or opinion so that it can lead to a solutive and positive goal. Interpersonal communication between parents and children can affect the success of children's education. During the COVID-19 pandemic, children's face-to-face learning was shifted to online, this tightened the role of parents in supervising their children because children were required to use automatic gadgets for children to deal directly with the online world for quite a long time. Therefore, the results of research from three family informants show that the role of parents is very important in different ways in each family, some interpersonal communication roles are associated with several functions including affective functions (affection), educational functions, religious functions, protective functions and recreational functions, which helps researchers find out how the role of each dual career marriage parent in supervising children's online learning and from four types of families there are only three types of family that occur in three family informants, namely consensual, pluralistic, protective, none of which is in the tolerant category. This research was conducted in Surabaya using a qualitative descriptive approach and phenomenological methods. The results showed that the type of family determines how the role of parents' interpersonal communication with their children because the role of parents' interpersonal communication in supervising children's learning has an impact on the success rate of children's education.